3. Some Remarks on Jesuitical sources for the History of Astronomy - Haddad, Thomás A. S.; Gonçalves, Carlos H. B. (Circumscribere International Journal for the History of Science, 2008)
In this article we present considerations on some elements corresponding to the guiding lines of the Workshop “Documents, Methods and Identity of the History of Science”. They arise from our research experience in history of astronomy and the problems we find when dealing with documents (in our case, the product of Jesuit astronomers in the 16th and 17th centuries). We argue that when attempting to give meaning to and raise questions on selected documents unavoidably we must inquire whether there was a characteristically Jesuit astronomy, even though it is not yet possible to attempt a satisfactory answer. The search for a finer understanding of this problems allows us to observe the operation of all three analytical and interpretative spheres suggested by Alfonso-Goldfarb in her article published in this issue of Circumscribere.